Bridging the Knowing–Doing Gap in Santri Worship Practices: A Systematic Literature Review Based on Attribution Theory - Veggy Xandrinata Unggari; Abdul Aziz (Faculty of Education and Teaching Training, Islamic State University of Kiai Haji Achmad Siddiq Jember, 2026)
The consistency of worship practices is widely regarded as a key indicator of the success of pesantren education in fostering santri's religious character. However, numerous studies have reported that some santri experience a decline in worship discipline when transitioning from the highly structured pesantren environment to family and community settings characterized by lower levels of supervision and different religious cultures. This phenomenon reflects a knowing–doing gap, in which religious knowledge is not consistently translated into practice. This study aims to examine the theoretical relationships among fiqh al-ibadah understanding, religious motivation, and worship consistency from the perspective of Attribution Theory. The study employed a Systematic Literature Review (SLR) following the PRISMA framework, synthesizing 27 peer-reviewed studies published between 2020 and 2026 retrieved from Scopus, Google Scholar, and SINTA databases. The findings reveal that worship consistency is influenced not only by religious knowledge but also by attributional orientation and motivational processes. Santri who attribute worship to internal factors, such as faith, spiritual awareness, and personal responsibility, are more likely to develop intrinsic religious motivation and maintain worship practices across different social environments. In contrast, external attribution based on institutional regulations, supervision, and social pressure tends to generate controlled motivation and contributes to the persistence of the knowing–doing gap. The novelty of this study lies in the development of an attribution-based framework that integrates an understanding of fiqh al-ibadah, value internalization, attributional orientation, and religious motivation to explain worship consistency among santri. The study contributes to Islamic educational psychology by extending Attribution Theory within pesantren education and providing a conceptual foundation for strengthening sustainable religious character formation.